Polygenic risk score for hypercholesterolemia in a Brazilian familial hypercholesterolemia cohort - Isabella Ramos Lima; Mauricio Teruo Tada; Theo G.M. Oliveira; Cinthia Elim Jannes; Isabela Bensenor; Paulo A. Lotufo; Raul D. Santos; Jose E. Krieger; Alexandre C. Pereira (Atherosclerosis Plus, 2022)
Background and aims: Familial hypercholesterolemia (FH) is a genetic disorder characterized by high levels of LDL-C leading to premature cardiovascular disease (CAD). Only about 40% of individuals with a clinical diagnosis of FH have a causative genetic variant identified, and a proportion of genetically negative cases may have a polygenic cause rather than a still unidentified monogenic cause. This work aims to evaluate and validate the role of a polygenic risk score (PRS) associated with hypercholesterolemia in a Brazilian FH cohort and its clinical implications. Methods: We analyzed a previously derived PRS of 12 and 6 SNPs (Single Nucleotide Polymorphism) in 684 FH individuals (491 mutation-negative [FH/M−], 193 mutation-positive [FH/M+]) and in 1605 controls. Coronary artery calcium (CAC) score was also evaluated. Results: The PRS was independently associated with LDL-C in control individuals (p < 0.001). Within this group, in individuals in the highest quartile of the 12 SNPs PRS, the odds ratio for CAC score >100 was 1.7 (95% CI: 1.01–2.88, p = 0.04) after adjustment for age and sex. Subjects in the FH/M− group had the highest mean score in both 12 and 6 SNPs PRS (38.25 and 27.82, respectively) when compared to the other two groups (p = 2.2 × 10-16). Both scores were also higher in the FH/M+ group (36.48 and 26.26, respectively) when compared to the control group (p < 0.001 for the two scores) but inferior to the FH/M− group. Within FH individuals, the presence of a higher PRS score was not associated with LDL-C levels or with CAD risk. Conclusion: A higher PRS is associated with significantly higher levels of LDL-C and it is independently associated with higher CAC in the Brazilian general population. A polygenic cause can explain a fraction of FH/M− individuals but does not appear to be a modulator of the clinical phenotype among FH individuals, regardless of mutation status.